Improving Employee Performance: The Role of Leadership, Work Environment, and Internal Control Systems Mediated by Work Motivation in the Papua Provincial Inspectorate - Selvi Lumempouw Selvi; Balthazar Kambuaya; Westim Ratang; Elsyan R. Marlissa; Vince Tebay; Arius A. Kambu (Golden Ratio of Data in Summary, 2026)
This study investigates the influence of leadership, work environment, and internal control systems on employee performance mediated by work motivation in the Papua Provincial Inspectorate, both partially and simultaneously. This study uses a quantitative approach with respondents from the Papua Provincial Inspectorate. Data analysis was conducted using regression analysis and path analysis to test the direct and indirect relationships between variables. The results show that leadership has a positive effect on work motivation with a coefficient of 0.213, the work environment has a positive effect with a coefficient of 0.325, and the internal control system also has a positive effect on work motivation with a coefficient of 0.018. Furthermore, leadership, work environment, and internal control systems are proven to have a partial positive effect on employee performance. Simultaneously, these three variables have a significant effect on employee performance through the mediating role of work motivation. These findings confirm that work motivation plays a strategic role in strengthening the influence of leadership, work environment, and internal control systems on employee performance. In practical terms, the results of this study provide an empirical basis for the Papua Provincial Inspectorate in formulating managerial policies oriented towards continuous improvement of employee performance.